The importance of accounting disclosure of social responsibility And its impact on achieving sustainable development by applying to the Saudi Paper Manufacturing Company in the Kingdom of Saudi Arabia (case study from 2021-2022) - Ismaiel, Salwa Hussien Roshdy (Journal of Economic, Administrative and Legal Sciences, 2023)
This research aimed to clarify the importance of accounting disclosure on social responsibility and its impact on achieving sustainable development. In completing this research, the researcher relied on the quantitative method, questionnaire and regression analysis in testing hypotheses, analyzing the sample, unloading, tabulating and analyzing data, and representing the research community in a random sample, which was randomly selected To the employees of the Saudi Paper Industry Company, 145 survey lists were sent and 120 lists were answered, and the researcher concluded that there is a statistically significant effect of accounting disclosure on social responsibility and achieving the dimensions of sustainable development for the company, by 27.1% at a significant level of 0.05, There is also a statistically significant effect of the accounting disclosure of social responsibility and the achievement of the economic dimension of the company’s sustainable development by 24.7% at a significant level of 0.05, and there is a statistically significant effect of the accounting disclosure of social responsibility and the achievement of the social dimension of the company’s sustainable development with a statistical significance of percentage 21.0% at the level of significance of 0.05, and there is a significant effect of statistical significance for the accounting disclosure of social responsibility and the achievement of the environmental dimension of sustainable development of the company by 20.5% at the level of significance of 0.05, The study recommended the need to pay attention to the disclosure of how waste management and methods of waste disposal in separate clarifications for industrial companies, the need to pay attention to the disclosure of the environmental cost in the financial statements and to conduct future research to show the impact of green accounting on achieving sustainability.